(untitled) (Global Journal of Science Frontier Research, 2012)
Bianchi type-VI 0 cosmological models of the universe filled with dark energy with constant and time-dependent equation of state parameters are investigated in general relativity. We obtain exact solutions of Einstein’s field equations using the condition that the shear scalar is proportional to the expansion scalar, which represent singular and non-singular cosmological models of the universe. The physical behavior of the models are discussed. We conclude that the universe models do not approach isotropy through the evolution of the universe.